Use of 18F-fluorodeoxyglucose positron emission tomography to standardize clinical trial recruitment in Takayasu's arteritis. (12th January 2022) - Quinn, Kaitlin A; Alessi, Hugh D; Ponte, Cristina; Rose, Emily; Ahlman, Mark A; Redmond, Christopher; Luo, Yiming; Bolek, Ertugrul Cagri; Langford, Carol A; Merkel, Peter A; Grayson, Peter C
Abstract: Objectives: To assess whether data from 18 F-fluorodeoxyglucose (FDG) PET should be incorporated into eligibility criteria for clinical trials in Takayasu's arteritis (TAK). Methods: The study was conducted in two parts. Part one was an international online survey among physicians with experience managing TAK to determine, using clinical vignettes, whether FDG-PET data influence decisions about enrolment in trials. Part two used patient data from an observational cohort study in TAK to assess agreement regarding decisions about enrolment into trials, based on clinical assessment with and without incorporation of FDG-PET data. Results: In part one, 68 physicians responded to the survey. Most physicians had used FDG-PET to diagnose TAK (82%) or monitor disease activity (66%). In vignettes representing active clinical disease, FDG-PET findings increased physician confidence in disease assessment and reduced outlier assessments. The greatest variability in decisions regarding enrolment into trials was observed in vignettes representing constitutional symptoms alone and elevated acute-phase reactants. In these cases, FDG-PET findings influenced decisions about enrolment and improved physician confidence. In multivariable models, FDG-PET findings were 1.29 times more strongly associated with enrolment decisions compared with levels of acute-phase reactants. In part two, incorporation of FDG-PET data significantly improved agreement about enrolment decisions between raters [inter-rater reliability (IRR) = 0.68 (95% CI 0.67, 0.69) to IRR = 0.88 (95% CI 0.87, 0.89); P < 0.01]. Conclusions: Incorporation of FDG-PET data into assessment of TAK influences decisions about enrolment of patients into trials, improves physician confidence about clinical assessment and could help reduce variability in study populations. Future trials in TAK should consider incorporating FDG-PET data into eligibility criteria.